Kondisi Sosial Ekonomi Anggota Kelompok Tani Hortikultura di Nagari Bungo Tanjuang, Kecamatan Batipuh, Kabupaten Tanah Datar - Suciana, Rahma; Iskarni, Paus (Lembaga Yasin AlSys, 2025)
This study aims to analyze the socio-economic conditions of horticultural farmer group members in Nagari Bungo Tanjuang and to identify the factors influencing their income. Horticultural farming is a strategic sector in the rural economy, requiring the optimization of both human and physical resources. A quantitative approach with a descriptive method was employed. Primary data were collected through questionnaires distributed to 35 farmer group members and analyzed descriptively and comparatively to reveal respondent profiles and inter-variable relationships. The results show that most farmers are in their productive age and have over 11 years of farming experience, although their educational backgrounds vary. Data analysis indicates a positive correlation between farmers’ income and factors such as land size, farming experience, and frequency of participation in training programs. Additionally, collective ownership of production assets by the farmer group serves as an essential form of physical capital supporting agricultural activities. The study concludes that farmers’ income is influenced by a combination of human capital namely experience and skill enhancement and physical capital, including land and production facilities. The findings underscore the importance of strengthening farmer group institutions as a key strategy for sustainably enhancing farmers' capacity and well-being.